Diagnostics and decision-making of the company management within the period of economiccrisis and recession - Pavel TOMŠÍK; Emil SVOBODA (Agricultural Economics (AGRICECON), 2010)
Enterprises are socio-economic entities with bonds to their environment. Their economic health is evaluated by the means of adequate diagnostic methods. When evaluating a processing business as a living organism, these diagnostic methods enable to determine their health condition. These business entities pass through individual stages of their life cycle and, in real time, their momentary condition corresponds with the homeostasis existing between the company's system and its environment. A diagnosis defined by the means of diagnostic methods must help to implement the goals which lead, on the base of business management activities, to the generation of an adequate response to the given momentary situation existing in the diagnosed enterprise. The definition of a proper diagnosis is important especially in those periods when the enterprise passes through its life crisis under the conditions of market recession. This scientific paper presents data formulated within the framework of research focused on the analysis of managerial, financial and economic risks and on the methods of their solution within the framework of strategic business management in a new business environment as influenced by the phenomena resulting from the integration processes, development of information technologies and factors of globalisation. This diagnostic method was applied when analysing in detail the operation of a company producing bioveterinary drugs and preparations. Keywords: diagnostics; homeostasis; crisis management; business environment